In Favor of an Alternative Evaluation Policy for University Faculty: An Interview with Hugo Aboites - Edna Luna Serrano (Universidad Autónoma de Baja California, 2004)
Since the nineties, one of the most important changes in the operation of Mexican universities has been the instrumentation of governmental regulation devices, based on the articulation of evaluation procedures, extraordinary financing programs and specific requirements to the institutions. In a scenario of financial contraction, and seeking greater efficiency and productivity of public expenditure, evaluation processes were implemented. The literature on the subject supports the power of evaluation programs under this policy to guide academic activities; nevertheless, there is no evidence of their effect in improving the substantive functions of universities. In this context, it is fundamental for academics to discuss alternative evaluation modes aiming at improving the quality of institutions.